Resilience in Times of Crisis: Testing Social Mobilization in Low-Income Neighbourhoods in Cali, Colombia, During the COVID-19 Pandemic Crisis (2020-2022) - Zapata Alvarez, Carlos Jose (Université d'Ottawa / University of Ottawa, 2023)
This thesis aims to analyze how low-income communities in Cali, Colombia, responded to the pressures and constraints of the COVID-19 pandemic crisis of 2020 and 2021. The emergency measures that the Colombian government implemented to contain the spread of the COVID-19 virus, such as lockdowns and quarantines, as well as the increase on violence from state actors and illegal armed organizations during the summer of 2021, put unprecedented pressures and constraints upon low-income communities in Cali. For this reason, this thesis investigates how civil society groups in low-income communities in the Highlands and in the Agua Blanca District in Cali organized and mobilized during the pandemic crisis to respond to these challenges. This thesis uses ethnographic methods to explore how low-income communities in Cali engaged in processes of social mobilization during the pandemic crisis, giving special attention to the neighbourhoods of Polvorines, Pampas del Mirador, Alto Jordan, and Potrero Grande. This thesis also investigates particular forms of social organization that low-income communities in Cali employed during the pandemic crisis, such as community kitchens.
Keywords: social mobilization in Latin America; social mobilization in times of crisis; social movements; state violence in Colombia; social resilience